Chiari Pelvic Osteotomy for Advanced Stage Osteoarthritis of the Hip Joint - YAMADA, Harumoto (Japanese Journal of Rheumatism and Joint Surgery, 1992)
Twenty-five Chiari pelvic osteotomies for advanced stage osteoarthritis of the hip joint were studied with follow-up periods of 4.1 years on an average. The mean Japanese Orthopaedic Association score was 63 before surgery and 87 after. Postoperative remodeling of the acetablum was classified according to X-ray findings, and there was significant correlation between the degree of acetabular remodeling and acetabular head index (AHI) . The hips with non-spherical heads showed better acetabular remodeling than the hips with spherical heads. These observations suggest that Chiari pelvic osteotomy is useful for advanced stage osteoarthritis of the hip joint.